Relationship between Self-Concept and Commitment to Assignments Work Motivation of Citizens Learning in Shopy Course and Training Institutions Tanjung Balai City - Rusydi Ananda; Shopiana Shopiana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this study was to find out: (1) a positive and significant relationship between self-concept and work motivation of the learning citizens, (2) a positive and significant relationship between commitment to the task and work motivation of the citizens, and (3) a positive and significant relationship between self-concept and commitment to the task together with the work motivation. The study population was all citizens learning 54 Tanjung Balai City Course and Training Institute, totaling 54 people. The entire population was sampled as a study. The research instrument used was a Likert scale questionnaire. Requirement test is performed to test the normality, linearity, and independence of the independent variables. Data analysis techniques used correlation and regression and simple correlation and regression and multiple correlations at the significance level α = 0.05. The research findings show: (1) there is a positive and significant relationship between self-concept and the work motivation of citizens learning. It means that the higher and more positive self-concept, the higher and more positive is work motivation by making an effective contribution of 13.82%. (2) There is a positive and significant relationship between commitment to the task and work motivation of citizens learning. This means that the higher and more positive the commitment to the task, the higher and more positive is the work motivation of the citizens learning by making an effective contribution of 8.74%, and (3) there is a positive and significant relationship together between self-concept and commitment to the task with the work motivation of citizens learning. This means that the higher and more positive the self-concept and commitment to the task, the higher and more positive is the work motivation of the citizens studying the Tanjung Balai Shopy Course and Training Institute by making an effective contribution of 22.60%.